2002
DOI: 10.4049/jimmunol.169.2.1058
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Production of IFN-γ by Macrophages Controls Their Recruitment to Kidney and the Development of Glomerulonephritis in MRL/lpr Mice

Abstract: Anti-DNA autoantibody production is a key factor in lupus erythematosus development; nonetheless, the link between glomerular anti-DNA autoantibody deposition and glomerulonephritis development is not understood. To study the inflammatory and destructive processes in kidney, we used IFN-γ+/− MRL/lpr mice which produce high anti-DNA Ab levels but are protected from kidney disease. The results showed that defective macrophage recruitment to IFN-γ+/− mouse kidney was not caused by decreased levels of monocyte che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 35 publications
(37 reference statements)
3
62
0
Order By: Relevance
“…Otherwise, blockade of CCR1 could selectively halt interstitial leukocyte recruitment and fibrosis but not glomerular injury in MRL/lpr mice (39). Some published studies demonstrated that CD4ϩ T cells were major infiltrating cells in glomeruli, whereas F4/80ϩ macrophages were predominant in the interstitium of both MRL/lpr mice and lupus-prone NZM2328 mice (40,41). Thus, we reasoned that differential effects of SM934 on autoantibody production and inflammatory leukocyte migration and/or function will result in differential therapeutic effects on glomerular and interstitial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, blockade of CCR1 could selectively halt interstitial leukocyte recruitment and fibrosis but not glomerular injury in MRL/lpr mice (39). Some published studies demonstrated that CD4ϩ T cells were major infiltrating cells in glomeruli, whereas F4/80ϩ macrophages were predominant in the interstitium of both MRL/lpr mice and lupus-prone NZM2328 mice (40,41). Thus, we reasoned that differential effects of SM934 on autoantibody production and inflammatory leukocyte migration and/or function will result in differential therapeutic effects on glomerular and interstitial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IFN-c receptor -/-MRL/lpr mice developed scleroderma-like disease, suggesting a protective role for IFN-c in fibrotic diseases [58]. IFN-c +/-MRL/lpr mice produced high anti-DNA antibody levels but were protected from kidney disease, suggesting a protective role with moderate IFN-c production [59]. Therapeutic benefits from IFN-c production were supported further by Ring et al [60], who demonstrated that IFN-c had a protective role in immunologically mediated glomerulonephritis initiated by foreign antigens.…”
Section: Discussionmentioning
confidence: 99%
“…by infiltrating macrophages is critical for the development of macrophage infiltration and development of lupus nephritis in IFN-␥Ϫ/Ϫ MRL/lpr mice (27). Although, whether the IFN-␥ producing cells seen in the kidney 4 mo after adoptive transfer of IFN-␥ ϩ/ϩ Mac-1ϩ spleen cells into IFN-␥Ϫ/Ϫ mice were macrophages or some other cell type(s) arising from the transfer was not determined (27).…”
Section: Discussionmentioning
confidence: 99%
“…Although, whether the IFN-␥ producing cells seen in the kidney 4 mo after adoptive transfer of IFN-␥ ϩ/ϩ Mac-1ϩ spleen cells into IFN-␥Ϫ/Ϫ mice were macrophages or some other cell type(s) arising from the transfer was not determined (27). IFN-␥ production by NR8383 cells is not a mechanism for increased glomerular recruitment of transferred macrophages in our study since IFN-␥ mRNA was detected by RT-PCR in endotoxin-stimulated NR8383 cells, but not in unstimulated or IFN-␥-stimulated cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%